CANNY OPERATOR'S IMPLEMENTATION OF IMAGE SEGMENTATION - Pristiwanto Pristiwanto (Sean Institute, 2020)
The process of segmentation in digital images that separates an object from the background or background can be obtained from the RGB value of each pixel in the digital image so that the object can be processed for other purposes. As technology develops in applications that process digital images, segmentation is becoming increasingly necessary. The results of segmentation must also be more accurate because if the results of segmentation are inaccurate it will affect the results of the next process. In general, the segmentation process is divided into three parts based on classification, by edge, and by region. the process starts with inputting a digital image and then the grayscale process is carried out. Next, choose the method then do the edge detection process with the Canny or Laplacian operator and finally the dilation procccess